Arab Nationalism - Tibi, B. author. aut Link
XVIII, 325 p.
Keywords: In this new edition Professor Tibi analyses the impact and function of nationalism and its contribution to social and political change in the Third World, taking the rise of nationalism in the Middle East as a historical example. He concentrates on the period after the First World War, when many Arab intellectuals became disillusioned with Britain and France as a result of the occupation of their countries. Professor Tibi's careful study of the writings and influence of Sati' al-Husri illustrates the connection between modern Arab nationalism and nineteenth century German Romantic nationalism, which will be of particular interest to the English reader. Professor Tibi concludes that while nationalism has played a necessary and important role in the movement for national independence in the Middle East, it has since developed into an ideology which seems to obstruct further social and political emancipation. This book will be of particular interest to historians and social scientists as well as to specialists in the area itself.